SimSchool: An Opportunity for Using Serious Gaming for Training Teachers in Rural Areas - Tyler-Wood, Tandra; Estes, Mary; Christensen, Rhonda; Knezek, Gerald; Gibson, David (2017)
This article examines the use of simSchool as a training tool for educators working with students with special needs in rural districts. SimSchool is a game which emulates a classroom utilizing a virtual environment. The theory supporting simSchool is explored and current research associated with simSchool is reviewed. The issues surrounding retaining quality special educators in rural districts are discussed. The potential for using simSchool for working with rural special education teachers is explored.